Analisis faktor efektivitas komunikasi pemasaran pada lokasi proyek properti Citraraya Tangerang - Tan, Ellys; Teofilus, Teofilus; Bernardus, Denny; Sarwoko, Endi (MBR (Management and Business Review), 2024)
This research aims to analyze factors in the effectiveness of marketing communication that can increase consumer interest in visiting property projects. This research was conducted in the context of property or real estate using a framing theory that the way we present information affects the way people perceive and take action.  The method used in this research is a descriptive quantitative research method using questionnaires as research instruments and Exploratory Factor Analysis. The targeted respondents with age above 25 years,  income above ten million rupiah and domiciled in Jabodetabek and Java Island. Of the 300 questionnaires distributed, there were 200 valid respondent data and entered the target. This research is expected to contribute to property companies so that the factors resulting from the research can be used in marketing communications more effectively in increasing consumer interest in visiting the location. The results stated that the dimensions of location, price, facilities, reputation, environment, service, events, and influencers are valid as dimensions of factors attracting consumer visits.